Towards Practical Argumentation in Multi-agent Systems - Panisson, Alison R.; Meneguzzi, Felipe; Vieira, Renata; Bordin, Rafael H. (2015 Brazilian Conference on Intelligent Systems (BRACIS), 2015)
Argumentation is a key technique for reaching agreements in multi-agent systems. However, there are few practical approaches to develop multi-agent systems where agents engage in argumentation-based dialogues. In this paper, we give formal semantics to speech acts for argumentation-based dialogues in the context of an agent-oriented programming language. Our approach uses operational semantics and builds upon existing work that provides computationally grounded semantics for agent mental attitudes such as beliefs and goals. The paper also shows how our formal semantics can be used to prove properties of argumentation in multi-agent systems with direct reference to mental attitudes. We do so with an example of a proof sketch of termination of multi-agent dialogues under certain assumptions.